Journal of the institution of engineers (India): Series A : Civil, Architectural, Environmental and Agricultural Engineering (Switzerland Springer)
This Journal serves the national and international engineering community through dissemination of scientific knowledge on practical engineering and design methodologies pertaining to civil, architectural, environmental and agricultural engineering. Original manuscripts are published on Peer review in all the areas including (but not limited to) structural designs, green buildings, environmental pollutions or agricultural crops related researches. It covers all possible areas of latest research and developmental works in the field of infrastructure developments, waste management techniques, harvestings methodologies, rainwater harvestings etc. so that the researchers, scientists or professionals can easily motivate themselves to pursue the work.